Gambaran Konsep Diri Suami yang Tidak menjadi Pencari Nafkah Utama - Prisilia Ongka Juniarta; Fransisca Rosa Mira Lentari (Humanitas (Jurnal Psikologi), 2020)
This study aims to understand male’s self-concept as a husband who is not the main breadwinner in his family, based on the self-concept theory from William H. Fitts (1971) who defines self-concept as the whole of one's consciousness or perception of himself, derived from the self observed, experienced, and valued by himself; and divides self-concepts into internal and external dimensions. The method used in this study is qualitative with phenomenology design, and the data collection was done by in-depth interviews. The participants of this study consisted of two men who were not the main breadwinners. The results show that both participants’ self-concept has a tendency to be negative in domain family self and social self. Both participants felt that their role fulfillment as head of household was not ideal with the wife's role dominating more. Both tended to be uncomfortable to talk about their conditions when interacting with the social environment. Keywords: self-concept; breadwinner; husband